2017
DOI: 10.3892/or.2017.5653
|View full text |Cite
|
Sign up to set email alerts
|

The circadian clock gene PER2 plays an important role in tumor suppression through regulating tumor-associated genes in human oral squamous cell carcinoma

Abstract: Abstract. Low expression of the clock gene PER2 is closely related to carcinogenesis and the development of cancer; however, the mechanism of the low expression of PER2 that led to cell malignant transformation remains unclear. This study used RNA interference (RNAi) technology to silence PER2 in SCC15 human oral squamous cell carcinoma (OSCC) cells. Then it was found that the ability of cancer cell proliferation, migration, and invasion were markedly increased (P<0.05), and the ability of cancer cell apoptosi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
24
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 37 publications
3
24
0
Order By: Relevance
“…Furthermore, in vitro investigations of PER2 overexpression in lung cancer LLC cells, breast cancer EMT6 cells, osteosarcoma MG63 cells, and pancreatic cancer Panc1 and Aspc1 cells have demonstrated significant increases in tumor cell apoptosis and marked decreases in cell proliferation (22)(23)(24). Our previous studies have also shown that knockdown of PER2 in OSCC cells can greatly enhance cell proliferation and reduce apoptosis (25,26). The aforementioned studies thus implicate PER2 as an important tumor-suppressor gene.…”
Section: Introductionmentioning
confidence: 86%
See 2 more Smart Citations
“…Furthermore, in vitro investigations of PER2 overexpression in lung cancer LLC cells, breast cancer EMT6 cells, osteosarcoma MG63 cells, and pancreatic cancer Panc1 and Aspc1 cells have demonstrated significant increases in tumor cell apoptosis and marked decreases in cell proliferation (22)(23)(24). Our previous studies have also shown that knockdown of PER2 in OSCC cells can greatly enhance cell proliferation and reduce apoptosis (25,26). The aforementioned studies thus implicate PER2 as an important tumor-suppressor gene.…”
Section: Introductionmentioning
confidence: 86%
“…Our previous studies found that downregulating PER2 in OSCC cells could markedly reduce cell apoptosis (25,26). Caspase-8 is an important apoptosis-related gene, and its abnormal expression is closely associated with carcinogenesis (45).…”
Section: Per2 Expressionmentioning
confidence: 99%
See 1 more Smart Citation
“…Considering this underpinning role for Otolin‐1 , any circadian regulation of the organic matrix must occur through interaction with this crucial molecule. We found both MMP 2 and TIMP 2 , proteins whose expression likely follows a circadian pattern as knockout studies of the clock gene PER2 have resulted in a shift in their levels . MMP 2 catalyses the cleavage of several types of collagen, including type X.…”
Section: Discussionmentioning
confidence: 88%
“…Finally, a new nomogram was generated combined risk score and clinicopathological characteristics. As displayed in the Figure 7A (31). With that in mind, disruption in timekeeping system could facilitate tumor progression(32), and circadian clock genes have also been reported to be involved in the carcinogenesis and prognosis of carcinomas (33), which may in turn contributes to the survival prognosis prediction and individualized medical treatment for patients.…”
Section: Patients Suffered From Unsatisfied Survival Time With Elevatmentioning
confidence: 99%